Ag@Au Bimetallic Nanoparticles: An Easy and Highly Reproducible Synthetic Approach for Photocatalysis - Barrías-González, P (Royal Society of Chemistry, 2022)
An Ag@Au bimetallic nanoparticle (BNP) formulation was developed in this work. The proposed formulation was developed using photochemical and chemical methods and non-toxic reagents, showing high reproducibility and homogeneity. The synthesized BNPs have an average size of 7 nm, a core-shell-like structure (silver core and gold shell), high colloidal and long-term stability, and superior catalytic activity under darkness and white light irradiation conditions when evaluating the reduction of 4-nitrophenol to 4-aminophenolate, with respect to the monometallic Ag and Au counterparts. Furthermore, BNP concentrations as low as 2 nM were required to reach 100% conversions in less than 30 minutes. Therefore, considering future applications, the high surface-to-volume ratio of the prepared BNPs coupled with their well-defined optical properties makes them a great candidate for developing heterogeneous catalyzer materials to be applicable under sunlight as an environmentally friendly catalytic system. © 2022 RSC.